Adolescents Who Self Harm: A Comparison of Those Who Go to Hospital and Those Who Do Not - Hawton, K; Rodham, K; Evans, E; Harriss, L (2009)
Background: Deliberate self harm (DSH) by adolescents is a major problem at both hospital and community levels although little is known about the factors associated with hospital presentation. Method: Using a community survey a comparison was undertaken of adolescents in 41 schools who reported DSH and presented to hospital with those who reported DSH but did not attend hospital. Results: While hospital presentation following DSH was associated with several factors, multivariate analysis indicated that the most important were method of DSH (overdose, methods other than self-cutting and multiple methods) and help-seeking before the act. Conclusions: The few differences between adolescents who present to hospital following DSH and those who do not, other than in method of DSH and prior help-seeking, highlight the need for primary preventive initiatives. © 2009 The Author. Journal compilation © 2009 Association for Child and Adolescent Mental Health.